Justice and security reform : development agencies and informal institutions in Sierra Leone - Denney, Lisa
"The book examines a post-conflict context often held up as an example of successful peacebuilding, and reveals how the politics of development agencies is an often forgotten constraint in security and justice reform and development efforts more broadly. Security and Justice Reform: Development agencies and informal institutions in Sierra Leone undertakes a deep contextual analysis of the reform of the countrys security and justice sectors since the end of civil war in 2002. Arguing that the political and bureaucratic nature of development agencies leads to a lack of engagement with informal institutions (such as chiefs and secret societies, who dominate the provision of security and justice to the majority of the population), this book examines the limited sustainability of transforming security and justice in fragile states. Security and Justice Reform provides an accessible account of one of the first countries to undergo development agency-led security and justice reforms. Particularly suited to upper-level undergraduates and postgraduate students, as well as practitioners working on security and justice issues, this book is relevant to those interested in security and justice reform and statebuilding, as well as Sierra Leones post-conflict recovery"--